As ações de educação ambiental em escolas rurais de Itabaiana-SE - Souza, Simone Marcela dos Santos (2014)
The Environmental Education actions are contained in the construction of values, attitudes, skills and abilities for the sake of conservation of the environment and human health. At school directors and teachers play a fundamental role in decision making, planning, organization, implementation and evaluation of actions may, in their practices, relate to Environmental Education to health as a way to promote in the school environment. This study aimed to analyze the actions of Environmental Education held in rural schools in Itabaiana - SE and its relation to health promotion. And the following objectives: a) determine whether the actions of Environmental Education and health promotion were included in the Political - Pedagogical Project (PPP) school; b) describe the characteristics of Environmental Education actions carried out in rural schools of Itabaiana - SE and its relation to health promotion; c) observe whether the school environment offering basic conditions for the occurrence of ealth promotion. Thus, we developed three instruments: the interview guide, the questionnaire and the observation script. The research was approved by the Ethics Committee, and Research at the University Federal of Sergipe (seems N° 483.783) is characterized as exploratory and descriptive. A total of ten directors and seventy-three teachers from ten rural schools. The first stage consisted of survey data on educacional institutions by the Municipal Itabaiana of Education and the second of two field visits to schools. During the field visit I was required in each school, the consent of direction for the research and access to the PPP. Additionally, observation was mad of the school environment, being recorded in the II field visit was handed the Informed Consent Term (IC) to interested participants; conduceted the interview with the directors and applied the questionnaire to teachers. The collected data were submitted to Bardin (2011) conten analysis and relative frequencies and percentages of categories, calculated with the aid of Excel software. The ratio of the shares of Environmental Education to the promotion of health has been indentified in four PPPs analyzed. The school environment proved to be appropriete, requiring adjustments in some schools in the aspects of reform, expansion and provision of toiletries. Regarding the actions of Environmental Education have been reported several initiatives involving issues related to health promotion, and most punctual. It was also reported the need for greater involvement of the school and the outside community, the greater availability of time for teachers to take these actions and increase the number of partner ships. It is expect that the results serve as indicators for the increase for Environmental Education actions related to health promotion in schools and encourage new studies on the subject.